A 20-year follow-up of a population sample (aged 25-34) including coal-miners and foundry workers in Staveley, Derbyshire. Issue 3 (August 1980) - Cochrane, A L; Moore, F
Abstract : A 20-year follow-up of a population sample of men aged 25-34 has been completed in Staveley, Derbyshire. The sample was based on a private census, with brief industrial histories, that enabled four groups to be established–"non-dusty, " "pure coal-mining, " "pure foundry, " and "other and mixed." The similarity of the mortality rates of non-dusty, coal-mining, and foundry groups is satisfactory, but there is, however, a surprisingly high mortality rate in the other and mixed group. We were unable to explain this on the basis of their industrial exposure, and only to a very limited extent by their smoking habits. We suggest that there is a small group of uncooperative men, overweight for their height and heavy smokers, who self-select themselves into jobs that are classified in a study such as this as other and mixed.